Isolation and tentative identification of antioxidative constituents from dichloromethane extract of muraya koenigii leaves using chromatographic technique / Norhakimy Abdul Majid and Aiza Harun - Abdul Majid, Norhakimy; Harun, Aiza (Universiti Teknologi MARA Cawangan Pahang, 2019)
This investigation aimed to identify antioxidative constituents from M. koeginii leaves using thin layer chromatographic (TLC) technique. The screening of phytochemicals was conducted using methanol extracts as well as the developed TLC of extracts. Isolation of antioxidative constituents was held using preparative TLC. Secondary metabolites that had been screened from methanol extract were recognized as tannins, alkaloids, flavanoid and terpenoids. Screening for phytochemical using developed TLC of extracts revealed the presence of antioxidative constituents from dichloromethane extract after spraying with DPPH reagent. The antioxidative constituents are proposed as (A) Cyclic Terpene ester,(B) 4-benzyloxy-4- [2,2,-dimethyl-4-dioxolanyl] butylaldehyde, (C) Oleic acid, (D) Piperidione (alkaloid derivatives) and (E) 9-oxo-methyl ester after analyzing with GCMS aided with Wiley Database matching individually. Based on its potent antioxidant properties, the use of M. koenigii leaves in the development of natural medicine for the treatment of various diseases cannot be neglected.